Effects of systemic isotretinoin treatment on hemogram, biochemical parameters, and inflammatory markers - Işıl Deniz Oğuz; Sevgi Kulaklı (Galenos Publishing House, 2024)
Background and Design: Isotretinoin, a vitamin A derivative, is widely used to treat moderate and severe acne. Although the effect of systemic isotretinoin treatment on hemogram parameters has been demonstrated, the results are still controversial. In the present study, we investigated the effect of isotretinoin on biochemical parameters, hemogram, and inflammatory markers in the Black Sea Region. Materials and Methods: Medical data of 300 patients with moderate and severe acne vulgaris who received systemic isotretinoin treatment for at least three months were analyzed retrospectively. Hemogram parameters, serum creatinine levels, liver transaminase levels, serum lipid levels, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio, and monocyte/high-density lipoprotein (HDL) ratios were evaluated before and three months after the treatment. Results: A significant decrease was found in leukocyte count, red blood cell count, neutrophil count, monocyte count, HDL levels, and NLR after three months of treatment compared to the baseline. A significant increase was found in platelet count, plateletcrit (PCT), platelet distribution width (PDW), red cell distribution width, hematocrit, mean erythrocyte hemoglobin, total cholesterol, low-density lipoprotein, triglyceride, and aspartate aminotransferase levels. Conclusion: According to our results, isotretinoin can affect several hemogram and biochemical parameters. In addition, this article is the only article demonstrating a decrease in monocyte count and an increase in PDW and PCT levels after the treatment of isotretinoin in the literature.